2016
DOI: 10.1242/dev.143768
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection disrupts neurovascular development and results in postnatal microcephaly with brain damage

Abstract: Zika virus (ZIKV) infection of pregnant women can result in fetal brain abnormalities. It has been established that ZIKV disrupts neural progenitor cells (NPCs) and leads to embryonic microcephaly. However, the fate of other cell types in the developing brain and their contributions to ZIKV-associated brain abnormalities remain largely unknown. Using intracerebral inoculation of embryonic mouse brains, we found that ZIKV infection leads to postnatal growth restriction including microcephaly. In addition to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
193
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(233 citation statements)
references
References 87 publications
15
193
0
6
Order By: Relevance
“…En este momento, no es posible explicar con claridad las anormalidades neurológicas y el síndrome de Guillain-Barré como efecto directo del virus; además, en el caso del síndrome, no es posible descartar una reacción cruzada entre algunos flavivirus, como el virus del dengue, y la ausencia de anticuerpos antiglucolípidos en pacientes en quienes dicho síndrome se manifestó tempranamente (4,49,50). Las diferencias observadas en los efectos de la infección por el ZIKV en el adulto y en el individuo en desarrollo sugieren que pueden existir diferentes factores que determinan el neurotropismo y la neurotoxicidad.…”
Section: Discussionunclassified
“…En este momento, no es posible explicar con claridad las anormalidades neurológicas y el síndrome de Guillain-Barré como efecto directo del virus; además, en el caso del síndrome, no es posible descartar una reacción cruzada entre algunos flavivirus, como el virus del dengue, y la ausencia de anticuerpos antiglucolípidos en pacientes en quienes dicho síndrome se manifestó tempranamente (4,49,50). Las diferencias observadas en los efectos de la infección por el ZIKV en el adulto y en el individuo en desarrollo sugieren que pueden existir diferentes factores que determinan el neurotropismo y la neurotoxicidad.…”
Section: Discussionunclassified
“…They also found that ZIKV induced the death of immature and mature neurons and reduced NPC proliferation and differentiation, which resulted in a thinner cortical layer. In both studies, there was no evidence of disruption of cortical lamination and the global transcriptome analyses of infected brains showed the upregulation of genes involved in immune-response-related and apoptosis pathways Shao et al, 2016). Wu et al (2016), however, found the virus mainly in the ventricular zone and striatum of postnatal day 1 mice that were infected at embryonic day 13.5.…”
Section: Immunocompetent Mouse Modelsmentioning
confidence: 91%
“…ZV kortikal gelişimin farklı evrelerinde etki ederek anormal hücre proliferasyonu/apoptoz, anormal nöronal migrasyon ya da anormal postmigrasyona neden olur (31). Diğer olası mikrosefali nedenleri, genetik anomaliler, gebelikte geçirilen bazı infeksiyonlar (STORCH: sifilis, toksoplazmoz, rubella, sitomegalovirus, herpes simpleks virusu, HIV ve diğer viruslar), annenin gebelikte toksinlere ve kimyasallara maruz kalması, fetal alkol sendromu, radyasyon, diabetes mellitus gibi metabolik hastalıklar, malnütrisyon, postpartum serebrovasküler ve nonvasküler (menenjit, ensefalit, bakır zehirlenmesi, kronik böbrek yetmezliği) hasarlardır (30,31).…”
Section: Zika Virusu Ve Mikrosefaliunclassified
“…Diğer olası mikrosefali nedenleri, genetik anomaliler, gebelikte geçirilen bazı infeksiyonlar (STORCH: sifilis, toksoplazmoz, rubella, sitomegalovirus, herpes simpleks virusu, HIV ve diğer viruslar), annenin gebelikte toksinlere ve kimyasallara maruz kalması, fetal alkol sendromu, radyasyon, diabetes mellitus gibi metabolik hastalıklar, malnütrisyon, postpartum serebrovasküler ve nonvasküler (menenjit, ensefalit, bakır zehirlenmesi, kronik böbrek yetmezliği) hasarlardır (30,31). Brezilya'da 2016 itibariyle ZV'ye bağlı 3530 mikrosefali ve 46 ölüm bildirilmiş-tir (32).…”
Section: Zika Virusu Ve Mikrosefaliunclassified